Analysis of the Association between Catechol‐O‐Methyltransferase Val158Met and Male Sexual Orientation. (7th September 2015) - Yu, Wei; Tu, Dan; Hong, Fuchang; Wang, Jing; Liu, Xiaoli; Cai, Yumao; Xu, Ruiwei; Zhao, Guanglu; Wang, Feng; Pan, Hong; Wu, Shinan; Feng, Tiejian; et al.
Abstract Introduction Male sexual orientation is thought to have a genetic component. However, previous studies have failed to generate positive results from among candidate genes. Catechol‐O‐methyltransferase (COMT), located on chromosome 22, has six exons, spans 27 kb, and encodes a protein of 271 amino acids. COMT has an important role in regulating the embryonic levels of catecholamine neurotransmitters (such as dopamine, norepinephrine, and epinephrine) and estrogens. COMT is also thought to be related to sexual orientation. Aims This study aimed to investigate the relationship between the COMT Val158Met variant and male sexual orientation. We performed association analysis of the COMT gene single nucleotide polymorphism, Val158Met, in 409 homosexual cases and 387 heterosexual control Chinese men. COMT polymorphism status was determined using a polymerase chain reaction‐based assay. Methods Polymerase chain reaction was performed to genotype the COMT Val158Met polymorphism. Main Outcome Measures The frequency differences of the genotype and alleles distribution between the male homosexual and control groups. Results Significant differences, both in genotype and alleles, between male homosexual individuals and controls indicated a genetic component related to male homosexuality. The Val allele recessive model could be an interrelated genetic model of the cause of male homosexuality. Conclusion The COMT Val158Met variant might be associated with male sexual orientation and a recessive model was suggested. Yu W, Tu D, Hong F, Wang J, Liu X, Cai Y, Xu R, Zhao G, Wang F, Pan H, Wu S, Feng T, and Wang B. Analysis of the association between catechol‐O‐methyltransferase Val158Met and male sexual orientation. J Sex Med 2015;12:1920–1926.